2021
DOI: 10.7759/cureus.20004
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Porocarcinoma Effectively Managed by Pembrolizumab

Abstract: Eccrine porocarcinoma (EPC) is a rare malignancy of the sweat glands. Currently, there is no standard algorithm for its presentations, diagnosis, and management. However, immunotherapy is an emerging option that may be crucial to the treatment of EPC. This report presents a case of a 79-year-old male who had a skin biopsy of an anterior scalp lesion, which revealed EPC. The patient underwent Mohs micrographic surgery to excise the tumor followed by two additional Mohs surgeries for recurrence and adjuvant radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Immunotherapy with pembrolizumab, which is a programmed cell death protein 1 (PD-1) inhibitor, could be a novel effective treatment for metastatic PC. Although cases are few (three cases), two cases with metastatic PC achieved good courses [ 58 , 67 , 75 ]. Lee et al reported the first PC case treated with pembrolizumab (Case #2) [ 58 ].…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapy with pembrolizumab, which is a programmed cell death protein 1 (PD-1) inhibitor, could be a novel effective treatment for metastatic PC. Although cases are few (three cases), two cases with metastatic PC achieved good courses [ 58 , 67 , 75 ]. Lee et al reported the first PC case treated with pembrolizumab (Case #2) [ 58 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…The tumor has been in remission for 22 months. A case reported by Singh et al has remained in partial remission for 18 months from the administration of pembrolizumab (Case #11) [ 67 ]. As seen above, pembrolizumab may have the potential to become an alternative treatment, or even a primary treatment, for metastatic PC.…”
Section: Treatmentsmentioning
confidence: 99%
“…One case reported by Lee et al received complete response for 16 months after switching to pembrolizumab (19). The other case reported by Singh et al showed partial remission for 18 months after the administration of pembrolizumab (20). Gupta reported that a patient who developed an eccrine carcinoma demonstrated a durable antitumor response after treatment with pembrolizumab (21).…”
Section: Discussionmentioning
confidence: 95%
“…However, limited cases with immunotherapy have been reported in SGC. Two cases with metastatic porocarcinoma obtained good results after being treated with pembrolizumab, which is a PD-1 inhibitor ( 19 , 20 ). One case reported by Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that hypermutated tumors are sensitive to immunotherapy, some authors have also evaluated its efficacy in EPC. In that direction, there have been reports of EPCs responding to anti-PD-1 therapy with nivolumab with or without prior anti-EGFR therapy with cetuximab, while some reports have demonstrated tumor response to pembrolizumab following progression to radiochemotherapy [ 30 , 31 , 62 ]. Although current evidence is limited, immunotherapy may represent a promising treatment option for advanced or metastatic EPCs, warranting further investigation.…”
Section: Treatmentmentioning
confidence: 99%